Morphology-Graded Silicon Nanowire Arrays via Chemical Etching: Engineering Optical Properties at the Nanoscale and Macroscale - Wendisch, Fedja J.; Abazari, Mehri; Mahdavi, Hossein; Rey, Marcel; Vogel, Nicolas; Musso, Maurizio; Diwald, Oliver; Bourret, Gilles R. (ACS Applied Materials and Interfaces, 2020)
We report on a quick, simple, and cost-effective solution-phase approach to prepare centimeter-sized morphology-graded vertically aligned Si nanowire arrays. Gradients in the nanowire diameter and shape are encoded through the macroscale substrate via a "dip-etching" approach, where the substrate is removed from a KOH etching solution at a constant rate, while morphological control at the nanowire level is achieved via sequential metal-assisted chemical etching and KOH etching steps. This combined approach provides control over light absorption and reflection within the nanowire arrays at both the macroscale and nanoscale, as shown by UV-vis spectroscopy and numerical three-dimensional finite-difference time-domain simulations. Macroscale morphology gradients yield arrays with gradually changing optical properties. Nanoscale morphology control is demonstrated by synthesizing arrays of bisegmented nanowires, where the nanowires are composed of two distinct segments with independently controlled lengths and diameters. Such nanowires are important to tailor light-matter interactions in functional devices, especially by maximizing light absorption at specific wavelengths and locations within the nanowires.
CRIS-Team Scopus Importer:2020-03-20
Keywords: colloidal lithography; graded substrate; KOH etching; metal-assisted chemical etching; Si nanowire arrays; structural colors